2019
DOI: 10.3892/mmr.2019.9972
|View full text |Cite
|
Sign up to set email alerts
|

Panax ginseng components and the pathogenesis of Alzheimer's disease (Review)

Abstract: Ginseng is one of the main representatives of traditional Chinese medicine and presents a wide range of pharmacological actions. Ginsenosides are the main class of active compounds found in ginseng. They demonstrate unique biological activity and medicinal value, namely antitumour, anti-inflammatory and antioxidant properties, as well as anti-apoptotic properties. Increasing levels of stress in life are responsible for the increased incidence of nervous system diseases. Neurological diseases create a huge burd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 137 publications
0
45
1
1
Order By: Relevance
“…Interestingly, with the multitarget and multicomponent treatment characteristics, TCM had unique advantages in dealing with AD [15,16]. It has been proven that Panax ginseng, one of the main representatives of TCM, was effective in treating AD, and the key mechanism has been revealed to be related to the PI3K/Akt signaling pathway [17]. A series of formula studies on the Panax ginseng/Polygala tenuifolia combination yielded varying improvements in the course of AD and the most representative formula was Kai-Xin-San (KXS), initially recorded in Bei Ji Qian Jin Yao Fang in Tang dynasty (AD 652) [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, with the multitarget and multicomponent treatment characteristics, TCM had unique advantages in dealing with AD [15,16]. It has been proven that Panax ginseng, one of the main representatives of TCM, was effective in treating AD, and the key mechanism has been revealed to be related to the PI3K/Akt signaling pathway [17]. A series of formula studies on the Panax ginseng/Polygala tenuifolia combination yielded varying improvements in the course of AD and the most representative formula was Kai-Xin-San (KXS), initially recorded in Bei Ji Qian Jin Yao Fang in Tang dynasty (AD 652) [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In the same line, fumarine has been reported to inhibit acetylcholinesterase activity and reduce memory impairment (Kim et al 1999). Furthermore, ginsenoside-rh4 was found to be involved in anti-inflammatory, antioxidant, and neuronal protection (Razgonova et al 2019;Wang et al 2019). Collectively, these findings suggested that the main KXS components are effective for treating AD.…”
Section: Discussionmentioning
confidence: 87%
“…e related effects of these six herbs in YZG have also been reported. Ginsenosides can reduce the formation of amyloid β-protein (Aβ) through inhibiting β-and c-secretase activity or by activating the nonamyloidogenic pathway, inhibit acetylcholinesterase activity and induced neurotoxicity, and reduce the generation of reactive oxygen species and neuroinflammatory response by Aβ [44,45]. Panax notoginseng can regulate the expression of AD-related circRNAs to achieve the therapeutic effect on AD [46].…”
Section: Discussionmentioning
confidence: 99%